ÜNİVERSİTE ÖĞRENCİLERİNİN İLETİŞİM BECERİLERİ ALGISI İLE KİŞİLERARASI İLİŞKİ BOYUTLARI ARASINDAKİ İLİŞKİNİN DEĞERLENDİRİLMESİ - (:unkn) unknown (My University, 2018)
Bu çalışmada üniversite öğrencilerinin iletişim becerileri algısı ile kişilerarası ilişki boyutlarıarasındaki ilişkinin değerlendirilmesi amaçlanmıştır. Araştırma grubu 2015-2016bahar döneminde Ankara ilinde bir devlet üniversitesinin iletişim fakültesinde eğitiminisürdüren (n=354) lisans öğrencileridir. Katılımcılardan veriler 25 maddeden oluşan “İletişimBecerileri Değerlendirme Ölçeği” ve 53 maddeden oluşan “Kişilerarası İlişki BoyutlarıÖlçeği” ile toplanmıştır. Kişilerarası İlişki Boyutları Ölçeği dört faktörlü yapıda olup“onay bağımlılık”, “empati”, “başkalarına güven” ve “duygu farkındalığı” boyutlarındanoluşmaktadır. Ölçeklerin her ikisi de 5’li Likert tiptedir. Çalışmaya katılan bireylerincinsiyetlerine göre, onay bağımlılık, empati, başkalarına güven, duygu farkındalığı veiletişim becerileri algıları toplam puan ortalamaları kadınların erkeklere göre anlamlıdüzeyde yüksek olduğu görülmüştür (p<.05). İletişim becerileri değerlendirme ölçeğitoplam puanı ile onay bağımlılık, empati, başkalarına güven ve duygu farkındalığı toplampuanları arasında anlamlı düzeyde doğrusal, aynı yönlü ve güçlü ilişki olduğu sonucunavarılmıştır (p<.05). Yani bireylerin iletişim becerileri değerlendirme puanları arttıkçaonay bağımlılık, empati, başkalarına güven ve duygu farkındalığı toplam puanlarının daarttığı söylenebilir.

This study has intended to evaluate the relationship between the communication skills perception of university students and interpersonal relationship aspects. The study group consists of the undergraduate students (n=354) continuing their education at the Faculty of Communication of a state university in Ankara in the spring period of 2015-2016. The data from participants has been collected using “Communication Skills Evaluation Scale” consisting of 25 items and “Interpersonal Relationship Aspects Scale” consisting of 53 items. Interpersonal Relationship Aspects Scale has a structure with four factors that consist of “approval dependence”, “empathy”, “trusting others” and “emotional awareness” aspects. Both scales are of Quintette Likert type. It has been seen that, according to genders of individuals participating in the study, the total score averages of female students in terms of approval dependence, empathy, trusting others, emotional awareness and communication skills perceptions are higher than those of male students significantly (p<.05). It has been concluded that there is a strong, significantly linear relationship in the same direction between the total score of the communication skills evaluation scale and the total scores of approval dependence, empathy, trusting others, emotional awareness (p<.05). Namely, it may be stated that the higher the evaluation scores of communication skills of individuals, the higher the total scores of approval dependence, empathy, trusting others, emotional awareness.
EVALUATION OF THE RELATIONSHIP BETWEEN THE COMMUNICATION SKİLLS PERCEPTION OF UNIVERSITY STUDENTS AND INTERPERSONAL RELATIONSHIP ASPECTS
Keywords: Eğitim, Eğitim Araştırmaları